2015
DOI: 10.1186/s12711-015-0089-5
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association analyses reveal significant loci and strong candidate genes for growth and fatness traits in two pig populations

Abstract: BackgroundRecently, genome-wide association studies (GWAS) have been reported on various pig traits. We performed a GWAS to analyze 22 traits related to growth and fatness on two pig populations: a White Duroc × Erhualian F2 intercross population and a Chinese Sutai half-sib population.ResultsWe identified 14 and 39 loci that displayed significant associations with growth and fatness traits at the genome-wide level and chromosome-wide level, respectively. The strongest association was between a 750 kb region o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 59 publications
3
57
0
1
Order By: Relevance
“…This heterogeneity may be caused by distinct mechanism of fat deposition for different types of adipose involving different microbes among abdominal adipose, leaf fat and subcutaneous adipose. This condition was similar to that in genetic dissection of porcine fatness traits, in which different genomic loci were identified for each fatness trait (Qiao et al, 2015). To the best of our knowledge, this study first evaluated the fatness-associated microbes in the cecum samples.…”
Section: Discussionmentioning
confidence: 62%
“…This heterogeneity may be caused by distinct mechanism of fat deposition for different types of adipose involving different microbes among abdominal adipose, leaf fat and subcutaneous adipose. This condition was similar to that in genetic dissection of porcine fatness traits, in which different genomic loci were identified for each fatness trait (Qiao et al, 2015). To the best of our knowledge, this study first evaluated the fatness-associated microbes in the cecum samples.…”
Section: Discussionmentioning
confidence: 62%
“…Expression of porcine PPARD inhibits the formation of myotube and increases adipocyte differentiation in mouse myoblasts [29]. In addition, several GWAS revealed the association of PPARD with limb bone length [30] and growth and fatness traits [31] in pigs. Similarly, HMGA1 which is located in a QTL region that we identified on SSC7 in Duroc, was reported to be associated with length of limb bone in pigs [30, 32] and height and length of hip axis in humans [24].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, several genes involved in the growth pathway were identified, such as IGF2BP2 , G H1 , CCND2 and MSH2 . The protein IGF2BP2 plays an important role in controlling the action of IGF [36] which are associated with growth and fatness traits in pigs [31]. Similarly, GH1 is necessary for growth promotion and energy metabolism regulation [37].…”
Section: Discussionmentioning
confidence: 99%
“…The most prospective and actual trend in farm animal breeding is studying gene polymorphisms affecting the productive traits (3,4). Over the last decade the interest of scientists has been focused on genes encoding growth factors, hormones, receptors, transport, and regulatory proteins (5,6).…”
Section: Introductionmentioning
confidence: 99%